Association Between Breastfeeding Success Rate and Nipple Length and Diameter in Thai Pregnant Women - Thanaboonyawat, Isarin; Chanprapaph, Pharuhas; Puriyapan, Amata; Lattalapkul, Jinda (Siriraj Medical Journal, 2020)
Objective: To demonstrate the average value of nipple length and diameter during the first and second half of gestation in Thai pregnant women, as well as its association with breastfeeding success rate. Methods: A total of 140 pregnant women attending the ANC unit at Siriraj Hospital were enrolled into this study during April to July 2008. They were divided equally into 2 groups by gestational age of less than 20 weeks and between 20-40 weeks, respectively. Demographic data, nipple length and width, areola width and breastfeeding success rate of each participant was retrieved for statistical analysis. Results: The mean nipple lengths of the first and second half of pregnancy were 0.79 ± 0.20 cm and 0.80 ± 0.18 cm, respectively, which were not statistically different. There was also no difference between the left and right side. The nipple width was 1.11 ± 0.27 cm. by average which did not change between gestations. The areola width increased significantly by gestational age but there was no difference between both sides. Breastfeeding success rate in mothers with nipple length of ≥0.7 cm of at least one side was greater than those with short nipples at both sides (86.6% and 58.8%, respectively). Forty four neonates (38.60%) with tongue tie were observed with 25 cases undergoing frenulotomy (56.81%). The breastfeeding success rate of newborns, tongue-tied newborns who underwent frenulotomy, and tongue-tied newborns without frenulotony was 84.3%, 84% and 73.7 %, respectively. Conclusion: Both nipple length and width did not increase along with gestation. Mothers with nipple length of 0.7 cm or more of at least one side could succeed in breastfeeding of 4.38 times greater than those with shorter nipple.